2018
DOI: 10.1136/tobaccocontrol-2018-054315
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of modified risk tobacco product claims on beliefs of US adults and adolescents

Abstract: ObjectiveUnder US law, tobacco product marketing may claim lower exposure to chemicals, or lower risk of health harms, only if these claims do not mislead the public. We sought to examine the impact of such marketing claims about potential modified risk tobacco products (MRTPs).MethodsParticipants were national samples of 4797 adults and 969 adolescent US smokers and non-smokers. We provided information about a potential MRTP (heated tobacco product, electronic cigarette or snus). Experiment 1 stated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 33 publications
3
43
0
1
Order By: Relevance
“…PMI’s own qualitative and quantitative studies consistently show that reduced exposure claims are likely to be perceived as reduced risk claims and will, therefore, mislead the public. While few studies outside the tobacco industry evaluated consumer perceptions of reduced risk or reduced exposure claims for non-cigarette tobacco products, 32 34 the results were similar. El-Toukhy et al 34 found that modified exposure claims reduced perceived risks of snus and e-cigarette products among adults and adolescents.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…PMI’s own qualitative and quantitative studies consistently show that reduced exposure claims are likely to be perceived as reduced risk claims and will, therefore, mislead the public. While few studies outside the tobacco industry evaluated consumer perceptions of reduced risk or reduced exposure claims for non-cigarette tobacco products, 32 34 the results were similar. El-Toukhy et al 34 found that modified exposure claims reduced perceived risks of snus and e-cigarette products among adults and adolescents.…”
Section: Discussionmentioning
confidence: 85%
“…While few studies outside the tobacco industry evaluated consumer perceptions of reduced risk or reduced exposure claims for non-cigarette tobacco products, 32 34 the results were similar. El-Toukhy et al 34 found that modified exposure claims reduced perceived risks of snus and e-cigarette products among adults and adolescents. These results indicate that perceptions of exposure and risk are highly correlated and communication about one—either lower risk or lower exposure—reduces perceptions of both risk and chemical exposure.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…When assessing how these claims of reduced risk and reduced exposure could impact consumers’ and possible consumers’ understanding and perceptions of IQOS, particular attention must be paid to the impact on youth as youth will likely not understand or will misinterpret these claims 4–6. Further, applicable law mandates that any advertising or labelling concerning products marketed with reduced exposure claims does not mislead consumers 7.…”
Section: Introductionmentioning
confidence: 99%
“… 27 50 51 Independent research also demonstrates that adults and adolescents misinterpret reduced-exposure claims as communicating lower risk even when there is no explicit claim of lower risk. 52 TPSAC also found that PMI failed to demonstrate that consumers would accurately understand the risks of IQOS as conveyed in PMI’s proposed MRTP labelling and advertising. 13…”
Section: Regulation Of Htps In the Usamentioning
confidence: 99%